Physical and Emotional Intimate Partner Violence and Women's Health in the First Year After Childbirth: An Australian Pregnancy Cohort Study. Issue 3 (February 2022) - FitzPatrick, Kelly M.; Brown, Stephanie; Hegarty, Kelsey; Mensah, Fiona; Gartland, Deirdre
Intimate partner violence (IPV) can comprise physical, sexual, and emotional abuse, and is a widespread public health concern. Despite increasing recognition that women experience different types of IPV, the majority of research has focused on physical IPV. The present study aims to examine associations between different types of IPV (physical, emotional, physical, and emotional) and women's mental, physical, and sexual health by analyzing longitudinal data from a prospective pregnancy cohort of 1, 507 first-time mothers in Melbourne, Australia. Questionnaires included validated measures of physical and mental health (Short Form Health Survey, Edinburgh Postnatal Depression Scale) and IPV (Composite Abuse Scale). Emotional IPV alone was the most commonly reported type of IPV ( n = 128, 9.5%), followed by both physical and emotional IPV ( n = 76, 5.7%), and then physical IPV alone ( n = 30, 2.2%). Women reporting emotional IPV or physical and emotional IPV had increased odds of poor health compared with women reporting no IPV. Experience of physical and emotional IPV was most strongly associated with mental health issues, including depressive symptoms (adjusted odds ratio [OR] 4.6, 95% confidence interval [CI] = [2.9, 7.1]) and self-reported anxiety (adjusted OR 2.9, 95% CI = [1.9, 4.4]). Experience of emotional IPV alone was associated with poor mental health as well as physical factors, including poor general physical health (adjusted OR 1.9, 95% CI = [1.2, 3.1]), and pain during sex (adjusted OR 1.8, 95% CI = [1.2, 2.7]). Increased odds of poor body image were also observed for women reporting emotional IPV alone and physical and emotional IPV. These findings highlight the need for greater awareness of the diversity in women's experiences of IPV among health care providers. This includes understanding the prevalence of emotional IPV among new mothers, and the range of health problems that are more common for women experiencing IPV.